Pengaruh Pemberian IAA Dan BAP Terhadap Pertumbuhan Vegetatif Timun Suri (Cucumis melo L.) Pada Sistem Aeoroponik - Zannah, Miftahul; Rahmadina, Rahmadina (Journal of Pharmaceutical and Sciences, 2026)
Suri cucumber (Cucumis melo L.) is a local horticultural commodity with high economic value; however, its productivity remains relatively low due to the use of conventional cultivation systems. This study aims to determine the effect of Indole Acetic Acid (IAA) and Benzyl Amino Purine (BAP) application and their interaction on the vegetative growth of Suri cucumber cultivated in a vertical aeroponic system. A factorial completely randomized design (CRD) with two factors was employed: IAA concentration (0, 50, and 100 ppm) and BAP concentration (0, 25, and 50 ppm), each with three replications. The observed parameters included plant height, number of leaves, and root length. Data were analyzed using two-way analysis of variance (ANOVA) followed by Duncan's Multiple Range Test (DMRT) at a 5% significance level. The results showed that the application of IAA and BAP significantly affected several vegetative growth parameters of Suri cucumber, particularly plant height. The interaction between IAA and BAP exhibited a synergistic response in enhancing vegetative growth in the aeroponic system. It can be concluded that the combination of IAA and BAP in a vertical aeroponic system has the potential to serve as an effective and sustainable alternative cultivation technology to increase Suri cucumber productivity.